2022
DOI: 10.1155/2022/3636481
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Dye Degradation Activity of Green Synthesized Iron Nanoparticles

Abstract: Nanoparticles have a wide range of applications in various fields such as cosmetics, pharmaceuticals, and agrochemicals. Synthesis of nanoparticles using plant extract is a very efficient, cost-effective, useful, and environmentally friendly method. A plant extract acts as a reducing agent in the formation of nanoparticles. Catharanthus roseus is one of the potential plants for biosynthesis of nanoparticles due to its easy availability. In the present study, the Catharanthus roseus plant extract was used to sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 24 publications
(31 reference statements)
1
22
0
Order By: Relevance
“…A number of studies have been reported including Ag: ZnO/lignin [ 19 ], La: ZnO/metasystox [ 21 ], Co: ZnO and Mn: ZnO/methyl orange [ 20 ], Cu: ZnO/crystal violet [ 18 ], Fe: ZnO, Mg: ZnO, and Ca: ZnO/phenol [ 22 ], nitrogen-doped ZnO/bisphenol A under visible light irradiation [ 25 ], Nb: ZnO/methylene blue under UV irradiation [ 24 ], and Ag: ZnO/rhodamine B under UV and visible light irradiation [ 23 ]. The photocatalytic activity of ZnO was enhanced by doping in all these studies.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been reported including Ag: ZnO/lignin [ 19 ], La: ZnO/metasystox [ 21 ], Co: ZnO and Mn: ZnO/methyl orange [ 20 ], Cu: ZnO/crystal violet [ 18 ], Fe: ZnO, Mg: ZnO, and Ca: ZnO/phenol [ 22 ], nitrogen-doped ZnO/bisphenol A under visible light irradiation [ 25 ], Nb: ZnO/methylene blue under UV irradiation [ 24 ], and Ag: ZnO/rhodamine B under UV and visible light irradiation [ 23 ]. The photocatalytic activity of ZnO was enhanced by doping in all these studies.…”
Section: Introductionmentioning
confidence: 99%
“…One such vegetable waste is onion, i.e., onion waste, which is commonly generated in every house, especially in a country like India. Onion is considered to have numerous phytochemicals, flavonoids, and enzymes that help in the synthesis of nanoparticles [ 17 , 18 , 19 ]. Alamdari et al, 2020 reported the synthesis and characterization of ZnONPs by using leaf extract of Sambucus ebulus.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructures are a scientific discipline that involves manipulating materials on a nanoscale level. Nanomaterials act like atoms because they have a larger surface area, enormous surface potential, and unique surface properties [1]. These nanosized materials exhibit high surface by volume ratios compared to bulk materials.…”
Section: Introductionmentioning
confidence: 99%
“…As an individual, they are helpful in various disciplines, including material science [3], photochemistry, medicine [4], and solar energy [5]. Calcium oxide (CaO) finds wide used in cosmetics, medicine, waste remediation, destructive adsorbent, and catalyst [1]. Chemical precipitation, hydrothermal, microemulsion, sol-gel, gas phase, microwave synthesis, and electrochemical methods have been described for CaO NPs synthesized and for other nanomaterials such as NiO, FeO, ZnO, Ag, and Au.…”
Section: Introductionmentioning
confidence: 99%